2006
DOI: 10.1385/criai:30:3:143
|View full text |Cite
|
Sign up to set email alerts
|

Beginning Antibiotics for Acute Rhinosinusitis and Choosing the Right Treatment

Abstract: Acute bacterial sinusitis (ABS) is an extremely common problem in both children and adults. There are three clinical presentations of acute sinusitis: (1) onset with persistent symptoms (nasal symptoms or cough or both for > 10 but < 30 d without evidence of improvement); (2) onset with severe symptoms (high fever and purulent nasal discharge for 3-4 consecutive days); and (3) onset with worsening symptoms (respiratory symptoms, with or without fever, which worsen after several days of improvement). Images to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…If fever is present in uncomplicated viral URIs, it tends to be present early in the illness, usually accompanied by other constitutional symptoms, such as headache and myalgia. 9,13,18 Generally, the constitutional symptoms resolve in the first 48 hours and then the respiratory symptoms become prominent. In most uncomplicated viral infections, including influenza, purulent nasal discharge does not appear for several days.…”
Section: Optionmentioning
confidence: 99%
See 1 more Smart Citation
“…If fever is present in uncomplicated viral URIs, it tends to be present early in the illness, usually accompanied by other constitutional symptoms, such as headache and myalgia. 9,13,18 Generally, the constitutional symptoms resolve in the first 48 hours and then the respiratory symptoms become prominent. In most uncomplicated viral infections, including influenza, purulent nasal discharge does not appear for several days.…”
Section: Optionmentioning
confidence: 99%
“…Accordingly, it is the concurrent presentation of high fever and purulent nasal discharge for the first 3 to 4 days of an acute URI that helps to define the severe onset of acute bacterial sinusitis. 13,16,18 This presentation in children is the corollary to acute onset of headache, fever, and facial pain in adults with acute sinusitis. The purpose of this key action statement is to discourage the practitioner from obtaining imaging studies in children with uncomplicated acute bacterial sinusitis.…”
Section: Optionmentioning
confidence: 99%
“…Wald suggested that ARS may appear in children with different presentations (8). The first consists of persistent symptoms and signs of an upper respiratory tract infection.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…According to this fact, a study performed in children with clinically, not radiographically, diagnosed acute rhinosinusitis showed that treatment with placebo, amoxicilline or amoxicillin‐clavulanate had similar effects with symptoms gradually improving within 14 days of initiation of treatment with no difference among the three treatment groups (9). Acute bacterial sinusitis can show up in three different ways: persistent nasal and respiratory symptoms with worsening after 10 days; severe symptoms onset (high fever of at least 38.5°C for at least 3–4 days despite uncomplicated viral upper respiratory infections, in which fever lasts less than 48 h, and purulent nasal discharge); biphasic disease with symptoms worsening on the sixth or seventh day of illness after an initial recovery (8). The bacterial super‐infection is most commonly caused by S. pneumoniae , H. influenzae , and M. catarrhalis .…”
Section: Systemic Acute Bacterial Sinusitis Therapymentioning
confidence: 99%